The Feminist Scenics:: theorizations about science and practice of the feminist theater scene and the space and importance of feminist epistemologies in the theatrical field - Romano, Lúcia Regina Vieira (Revista Brasileira de Estudos da Presença, 2024)
This article describes a feminist scenic, resulting from the application of feminist epistemologies to theater, synthesizing the criticism they make of the canonical demarcations linked to the act of knowing, which contribute to the invalidation of women's experience. Its way of functioning is associated with the awareness of gender hierarchies, to which it reacts through the formulation of poetic and political strategies to confront discriminatory and sexist social models and their symbolic supports. It is concluded that this feminist scenic finds centrality in pedagogy, where emancipatory forms of knowledge and territories of resistance and creation emerge, which give new meaning to being.